2009
DOI: 10.1155/2010/369141
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Thienopyrimidines and their Antipsychotic Activity

Abstract: A series of thienopyrimidines and related heterocycles were synthesized by refluxing related imidoyl chloride with primary and secondary amines under microwave irradiation and classical heating. The imidoyl chlorides were synthesized from corresponding cyclic imides with phosphorus oxychlorides under microwave irradiation and classical heating. The structures of the compounds were confirmed by FT-IR, NMR. The synthesized compounds were screened for anti psychotic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The inhibitors molecules induce cell death by trapping the gyrase DNA complex, inducing oxidative damage, and preventing DNA replication. 4 Thienopyrimidines represent important chemical class in drug discovery due to vast range of pharmacological properties including antiallergic, 5 antiviral, [6][7] anti-in-flammatory, [8][9][10][11][12] analgesic, [13][14] antispasmodic, antibacterial, [14][15] antifungal, 16 antimicrobial, [17][18][19][20][21] antidiabetic, 22 antioxidant, 23 antitumor, [24][25][26][27][28][29] antipsychotic 30 etc. This useful activity of thienopyrimidine generates our interest in developing a tool for screening novel thienopyrimidine analogs are promise antibacterial agent.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitors molecules induce cell death by trapping the gyrase DNA complex, inducing oxidative damage, and preventing DNA replication. 4 Thienopyrimidines represent important chemical class in drug discovery due to vast range of pharmacological properties including antiallergic, 5 antiviral, [6][7] anti-in-flammatory, [8][9][10][11][12] analgesic, [13][14] antispasmodic, antibacterial, [14][15] antifungal, 16 antimicrobial, [17][18][19][20][21] antidiabetic, 22 antioxidant, 23 antitumor, [24][25][26][27][28][29] antipsychotic 30 etc. This useful activity of thienopyrimidine generates our interest in developing a tool for screening novel thienopyrimidine analogs are promise antibacterial agent.…”
Section: Introductionmentioning
confidence: 99%
“… The vibration at 1670 cm –1 was ascribed to the ester carbonyl. This assignment was based on the known vibrations of similar compounds and from the calculated spectra of 1A and 2A . , This peak was consistent even after thermal annealing, and it provided sound evidence that the ester bond resisted polymerization. The imine CN vibration usually occurs at 1620–1680 cm –1 . However, it overlapped with the CO and aromatic vibrations, making it difficult to identify .…”
Section: Resultsmentioning
confidence: 73%
“…This assignment was based on the known vibrations of similar compounds and from the calculated spectra of 1A and 2A. 42,43 This peak was consistent even after thermal annealing, and it provided sound evidence that the ester bond resisted polymerization. The imine CN vibration usually occurs at 1620−1680 cm −1 .…”
Section: Resultsmentioning
confidence: 81%
“…It has been reported that nucleophilic substitution of chlorosubstituted derivatives with different aromatic amines could be operated in DMF. 46) Reacting equimolar amounts of 7a, b with anthranilic acid in DMF containing catalytic amounts of anhydrous potassium carbonate afforded the 4-anilino derivatives 8a, b.…”
Section: )mentioning
confidence: 99%